Significance of dermatoglyphics in criminalistic description of human appearance - Ye. V. Kalyanov (Bûlleten' Sibirskoj Mediciny, 2009)
Based on materials of combined anthropogenic enquiry of 2 620 men and 380 women, which included fingerprint and palmprint records, relations between dermatoglyphic and descriptive external characteristics have been studied with the aid of various statistical methods. The obtained data can significantly extend capabilities of expert examination concerning the criminalistic and medicolegal anthropometric identification in operational investigations.